ChemInform Abstract: Direct Catalytic Enantioselective Vinylogous Aldol Reaction of α‐Branched Enals with Isatins. Issue 11 (8th March 2013) - Cassani, Carlo; Melchiorre, Paolo
Abstract Prolinol‐catalyzed reaction of isatins with α‐alkylated enals provides a facile, regio‐, and highly enantioselective approach to 3‐hydroxyoxindoles of type (III) and (V).